Perception of Export Barriers in a High-Tech Sector in a Less Developed Country: The Case of ICT SMEs in Malaysia - Richardson, Christopher J. R. (The South East Asian Journal of Management, 2011)
This paper investigates which export barriers are most pressing to small and medium sized enterprises (SME) in a high-tech sector in a developing-country. It also examines whether exporters and non-exporters perceive different export barriers as being more pressing to their export development/initiation. The unit of analysis is SMEs in Malaysia’s information and communications technology (ICT) sector. The findings suggest that the high cost of exporting is the most severe problem facing firms in the sample, with cultural differences posing the least important obstacle. Furthermore, with just two exceptions, there are no statistically significant differences in the perceptions of export barriers between exporting and non-exporting firms.